Binocular indirect ophthalmo microscope-assistant gas-perfused pars plana vitrectomy: A novel technique for vitreous sample acquisition. Issue 49 (December 2016) - Zhang, Luyi; Yang, Xiaoli; Zheng, Qingqing; Wu, Miaoqin
Abstract : Abstract: The vitreous sample has been used for the diagnosis of uveitis and intraocular malignancy for decades. The sample volume is usually limited to 1 mL with current techniques. In the present study, a novel technique for higher amount of vitreous sample acquisition, that is, Binocular Indirect Ophthalmo Microscope-assistant gas-perfused pars plana vitrectomy (BAG-PPV) was invented. For diagnostic purpose, BAG-PPV with 23-ga vitrectomy system was performed on a 54-year-old Chinese male with the symptom of bilateral atypical uveitis. More than 3 mL of vitreous sample per eye was collected without any significant complications. Cytopathology was confirmed on the basis of cell surface markers and released cytokines by flow cytometry analysis and cytokine assays respectively. A monoclonal B-cell population with the pattern of CD5 −, CD10 −, cyKi67 +, CD71 +, FMC7 +, CD23 −, and kappa light chain single expression for the right eye and a monoclonal B-cell pattern with CD5 −, CD10 −, cyKi67 +, and kappa light chain restriction for the left eye were identified. The cytokine assay revealed high levels of interleukin (IL)-10 (90, 838.30 and 41, 098.0 pg/mL for the right and left eyes, respectively) and IL10/IL6 ratios for both eyes (with 90.78 and 63.26 for the IL10/IL6 ratios of the right and left eyes, respectively), while those for the cerebrospinal fluid were low (4.77 pg/mL for the IL10 level and 0.65 for the IL10/IL6 ratio). Based on the results, the patient was diagnosed with primary intraocular lymphoma for bilateral eyes. Our results demonstrated that diagnostic vitrectomy with BAG-PPV using the 23-ga vitrectomy system was safe, efficient, and able to provide useful diagnostic information for suspicious intraocular malignancy and other atypical uveitis. Abstract : Supplemental Digital Content is available in the text